1994
DOI: 10.1111/j.1432-1033.1994.tb18581.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxynaphthalene reductase involved in melanin biosynthesis in Magnaporthe grisea

Abstract: During the biosynthesis of fungal melanin, tetrahydroxynaphthalene reductase catalyzes the NADPH-dependent reduction of 1,3,6,S-tetrahydroxynaphthalene (T,HN) into (+)-scytalone and 1,3,8-trihydroxynaphthalene into (-)-vermelone. The enzyme from Magnaporthe grisea, the fungus responsible for rice blast disease, has been purified to homogeneity. It is a tetramer of four identical 30-kDa subunits. A full-length cDNA clone of about 1 kb encoding T4HN reductase has been isolated from a cDNA library constructed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
1
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 49 publications
1
103
1
2
Order By: Relevance
“…However, whereas the involvement of ver-1 in aflatoxin biosynthesis has been securely established in vivo, the function of its gene product has defied demonstration in vitro (48,56). VidalCros et al (34) observed a 56% protein sequence identity between VER-1 and scytalone reductase, an enzyme that catalyzes an aryl dehydroxylation in the biosynthesis of melanin. Furthermore, a 52% similarity exists between the ver-1 gene product and the presumed ketoreductase from the Streptomyces actIII gene (48).…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas the involvement of ver-1 in aflatoxin biosynthesis has been securely established in vivo, the function of its gene product has defied demonstration in vitro (48,56). VidalCros et al (34) observed a 56% protein sequence identity between VER-1 and scytalone reductase, an enzyme that catalyzes an aryl dehydroxylation in the biosynthesis of melanin. Furthermore, a 52% similarity exists between the ver-1 gene product and the presumed ketoreductase from the Streptomyces actIII gene (48).…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] The importance of melanin in infection structures is emphasized by the observation that knockout of genes in the melanin biosynthesis pathway leads to loss of the function of appressorium-mediated penetration and pathogenicity in M. oryzae. 31,34,35 Turgor pressure in the appressoria of melanin-deficient mutants is about 30-70% of that measured in fully melanized appressoria. 10 The force exerted during initial penetration of a single appressorium is substantial.…”
Section: Infection Structures Of Pathogenic Fungimentioning
confidence: 99%
“…This secondary metabolite is theorized to be important to the survival of these fungal groups (Sussman, 1968). Several genes involved in the melanin biosynthetic pathway have been analyzed, especially 1,3,8-trihydroxynaphthalene reductase genes: THR1 in Colletotrichum lagenarium (Perpetua et al, 1996), ThnR in Magnaporthe grisea (Vidal-Cros et al, 1994), Brn1 in Cochliobolus heterostrophus (ϭteleomorph of Bipolaris maydis) (Shimizu et al, 1997). Amino acid sequences of proteins encoded by these genes showed high homology through the entire sequence.…”
mentioning
confidence: 99%